Inclusive Education and Academic Achievement of Students with Visual Impairment: Challenges, Opportunities, and Evidence-Based Practices - Dheeraj Kumar Nagar; Mr. Hasan Deen Khan (RADJA PUBLIKA, 2026)
Inclusive education has become a central policy goal in special education systems worldwide, yet its implementation for learners with visual impairment continues to raise questions about access, equity, and academic outcomes. This paper reviews the theoretical foundations, empirical literature, and practical realities associated with educating students with visual impairment in general education classrooms. It examines the barriers that limit meaningful participation, including inaccessible curricula, insufficient teacher preparation, limited availability of adapted materials, and attitudinal obstacles among peers and staff. It also considers the opportunities that inclusive settings offer for social integration, self-determination, and exposure to grade-level academic content. Drawing on evidence-based practices such as expanded core curriculum instruction, universal design for learning, collaborative teaching models, and structured orientation and mobility programming, the paper proposes a framework for improving academic achievement while preserving the disability-specific supports that learners with visual impairment require. The discussion concludes that inclusion is not merely physical placement but a set of conditions that must be deliberately engineered, resourced, and monitored if it is to translate into improved literacy, numeracy, and long-term postsecondary outcomes for this population.